Alternative cleavage and polyadenylation in spermatogenesis connects chromatin regulation with post-transcriptional control. Issue 1 (December 2016) - Li, Wencheng; Park, Ji; Zheng, Dinghai; Hoque, Mainul; Yehia, Ghassan; Tian, Bin
Abstract Background Most mammalian genes display alternative cleavage and polyadenylation (APA). Previous studies have indicated preferential expression of APA isoforms with short 3' untranslated regions (3'UTRs) in testes. Results By deep sequencing of the 3' end region of poly(A) + transcripts, we report widespread shortening of 3'UTR through APA during the first wave of spermatogenesis in mouse, with 3'UTR size being the shortest in spermatids. Using genes without APA as a control, we show that shortening of 3'UTR eliminates destabilizing elements, such as U-rich elements and transposable elements, which appear highly potent during spermatogenesis. We additionally found widespread regulation of APA events in introns and exons that can affect the coding sequence of transcripts and global activation of antisense transcripts upstream of the transcription start site, suggesting modulation of splicing and initiation of transcription during spermatogenesis. Importantly, genes that display significant 3'UTR shortening tend to have functions critical for further sperm maturation, and testis-specific genes display greater 3'UTR shortening than ubiquitously expressed ones, indicating functional relevance of APA to spermatogenesis. Interestingly, genes with shortened 3'UTRs tend to have higher RNA polymerase II and H3K4me3 levels in spermatids as compared to spermatocytes, features previously known to be associated with open chromatin state. Conclusions Our data suggest that open chromatin may create a favorable cis environment for 3' end processing, leading to global shortening of 3'UTR during spermatogenesis. mRNAs with shortened 3'UTRs are relatively stable thanks to evasion of powerful mRNA degradation mechanisms acting on 3'UTR elements. Stable mRNAs generated in spermatids may be important for protein production at later stages of sperm maturation, when transcription is globally halted.